The Influence of Employee Welfare and Organizational Culture on Employee Loyalty: The Mediating Role of Employee Performance at Bank Aceh Syariah, Banda Aceh - Annur Jannah Reyza; Thasrif Murhadi; Febyolla Presilawati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to describe the state of employee well-being, organisational culture, performance and loyalty at Bank Aceh Syariah, as well as to analyse the influence of well-being and organisational culture on employee loyalty, both directly and indirectly via performance as a mediating variable. This study employs a quantitative approach using a survey method. The study population consists of 283 employees of Bank Aceh Syariah, and the entire population was sampled using a census technique. Data were collected through the distribution of a questionnaire designed based on the research variables’ indicators. Data analysis was conducted using Structural Equation Modelling (SEM) with the AMOS programme. The results of the study at Bank Aceh Syariah indicate that all variables fall into the good/high category, with a mean value of 3.78 for well-being, 3.61 for organisational culture, 3.91 for performance, and 3.65 for employee loyalty. Partially, well-being has a positive and significant effect on loyalty (p = 0.005) and on performance (p = 0.008). Organisational culture also has a positive and significant effect on loyalty (p = 0.003) and performance (p = 0.012). Performance has a positive and significant effect on employee loyalty (p = 0.000). In the mediation test, the direct effect of well-being on loyalty was -0.592, whilst the indirect effect via performance was 0.573 (0.503 × 1.141), indicating competitive mediation. Similarly, the direct effect of organisational culture on loyalty was -0.152, whilst the indirect effect via performance was 0.234 (0.206 × 1.141), which also indicates competitive mediation. The implications of this study confirm that improving welfare, strengthening organisational culture, and optimising performance management are key strategies for Bank Aceh Syariah to enhance employee loyalty in a sustainable manner.